"Come on f––er, just load!" Powerlessness, waiting, and life without broadband. Issue 6 (18th October 2022) - Mathews, Nick; Ali, Christopher
Abstract: Waiting is a way of experiencing the effects of power. This article finds those waiting for fixed broadband connection are powerless to end the waiting and increasingly frustrated with the powerful—the governmental officials, policy makers, and broadband providers—who control their waiting. This article, built on 19 interviews with residents of a rural county in the United States, details the lived experiences of those waiting for a fixed broadband connection and shines a critical light on the unequal power dynamics of digital inequality and waiting. The findings demonstrate residents suffer from "chronic waiting" for a connection. They also wait while using the internet, via inferior mobile connections, laboring through issues such as buffering. Finally, the findings illustrate the only way to avoid "technology-induced waiting" is to wait in alternative ways, including turning into a "second-shift" family to enjoy internet service in the middle of the night. Lay Summary: This research finds that waiting is a common, stressful, and vexing part of living without a fixed broadband connection. This article offers a deep and rare exploration of the inequalities facing those on the wrong side of the digital divide, demonstrating a painful feeling of powerlessness. Residents wait for a home broadband connection with no idea when their waiting will end. They wait while using the internet with poor connection speeds leading to buffering, lag, and slow download and upload speeds. To avoid these technology-induced types of waiting, residents wait in alternative ways. Most striking, this includes "second-shift" families that wait until the middle of the night to enjoy improved internet service and entertainment.